WORK POSTURE ANALYSIS USING APPROACH METHOD OF RAPID UPPER LIMB ASSESSMENT (RULA) AT FABRIC CUTTER WORKERS TO REDUCE MUSCULOSKELETAL DISORDERS (MSDS) (RANGGANESVI HOME INDUSTRY CASE STUDY) - Irmawati, Nur Ayu; Widhy Wahyani (Journal of Innovation Research and Knowledge, 2024)
Home Industry Convection Bag "Rangganesvi" is a Home Industry that produces various types of bags. Workers carry out the production process manually using makeshift work facilities that are not good because these workers sit hunched on the floor without a base for 8 hours of work. This problem is related to work postures that are not ergonomic. This can lead to complaints of Musculoskeletal Disorders (MSDs) which consist of bones and skeletal muscles that are conscious muscles. With these complaints, a Nordic Body Map (NBM) Questionnaire was filled out for 11 workers to know the body parts of the workers who felt sick while doing work at the work station. It was found that the most dominant body part of the risk of Musculoskeletal Disorders (MSDs) is the back. This is analyzed using the Rapid Upper Limb Assessment (RULA) method. The final score obtained for the cloth cutting process activity with the posture of sitting on the floor and doing cloth cutting manually gets a score = 6 and is at a risk level of 3 which indicates that further investigation is needed and changes are needed as soon as possible by using a Cloth Cutting Machine which gets a score = 3 and is at risk level 2. Thus it can reduce the risk of Musculoskeletal Disorders (MSDs)